The evolution of the participation and abstention of the Portuguese in parliamentary elections, 1975-1995 - Freire, André (2000)
In this article, we test the impact of the social structures and the economic conjuncture on electoral abstention by the Portuguese in parliamentary elections from 1983 to 1995. Our main conclusions are as follows. First, abstention continues to be fundamentally a product of the rural and peripheral nature of the municipalities. Second, this element has lost some of its importance in explaining abstention, especially in 1987 and 1991. Third, we conclude that this phenomenon represented a growth in «political abstention», that is, on the part of individuals that are well-integrated socially but are momentarily dissatisfied with the way the political system is working. Fourth, this growth in «political abstention» has had clear effects on party dynamics.